SEMIOTIC ANALYSIS OF MCDONALD’S PRINTED ADVERTISEMENT - URAIDA, SITI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Semiotic, printed advertisement, sign, icon, symbol, index, connotation, myth Printed advertisement has a promotional function as medium to advertise aproduct. It implicitly persuades people to create demand of product which is being advertised. In this study, the writer uses printed advertisement of McDonald’s fast food company as the object. The printed advertisement was analyzed by usingSemiotics study. There are seven printed advertisements that were analyzes in this study. All of the printed advertisements taken were under different themes ofpromotions. The themes are promotions on Opened New Store, Birthday Party, McBreakfast, Coffee, French Fries, Burger and Milkshake. There are threequestions to be answered: (1) What are the semiotic signs found in McDonald’sprinted advertisements?; (2) What are the connotations found in McDonald’s printed advertisements?; (3) What kind of mythical significationcould be interpreted in  McDonald’s logo?.This study uses qualitative approach by document analysis because the study focuses on identifying sign, interpreting connotation and interpreting mythfound in McDonald’s printed advertisements. The writer collected the data bylooking at the verbal and visual sign contained within the McDonald’s printedadvertisements. In analyzing the data, the writer applied Peirce’s typology of signtheory and also Barthes’ connotation and myth theories.The writer found that there were 66 signs in total consisting of 30 icons, 14 indexes and 22 symbols. Most of the connotation meanings of the printedadvertisements reflect a certain messages related to the theme or product that is promoted. Each sign has a very important role to build up expected additional ideaof the advertisement. It has function to make clear, support and strengthen up aparticular message. The logo of McDonald’s is considered to have strongest mythical signification because it always appears on all of McDonald’s advertisements. Moreover, by the time goes on the yellow colored capital letter“M” contains the myth of American culture way of life in terms of eating anddaily habits which lead Americans to be quick in anything.The writer suggests that the next researchers conduct a study on semiotics by using another form of advertisement. The next researchers are also suggested that they use some other theories to gain better understanding about semiotics.